Penyimpangan Seksual Menelusuri Kontroversi dalam Identitas LGBT - Annisa Hafid; Aulia Ratna Sari; Talisha Mustika Zahrani; Sri Mulyeni (Universitas Maritim AMNI Semarang, 2025)
LGBT identity has become a focus of debate that triggers controversy related to the conflict between ther ole of tradition and modernity in defending human rights, as well as sexuality. This research discusses the controversy generated by LGBT identity in society with the main focus on highlighting the different perspectives on LGBT identity and sexual orientation. Using various sources of articles and journals that have been analyzed for this research, the result show that controversies caused by LGBT groups are often due to the clash between traditional perspectives and modern views on identity and freedom of individual rights. This explains how diverse perspectives on objective content shape cultural discourse and influence wise behavior on matters related to human rights and social justice.